Physiology and biochemistry of human subjects during entrapment - Agapiou, A; Mikedi, K; Karma, S; Giotaki, Z K; Kolostoumbis, D; Papageorgiou, C; Zorba, E; Spiliopoulou, C; Amann, A; Statheropoulos, M (Journal of breath research, 2013)
A classification of various categories of entrapped people under the ruins of collapsed buildings after earthquakes, technical failures or explosions is proposed. Type and degree of injury at the moment of building collapse and duration of entrapment are the two basic parameters in this classification. The aim is to provide sources and types of volatile organic compounds (VOCs) that can be used for establishing a new method for locating entrapped victims based on human chemical signatures. Potential target compounds, among others, are ammonia, acetone, isoprene, dimethylsulfide, dimethyldisulfide and trimethylamine. In this context, the possible neuroendocrine, metabolic and physical responses of potential victims during the different types of entrapment are correlated with the sources of VOCs such as expired air, urine, blood and sweat. The proposed classification scheme was developed as part of an integrated research project which investigates the use of combined audio, video and chemical methods for the early location of entrapped people under the ruins of collapsed buildings.